Effect of conductive carbon material content and structure in carbon fiber paper made from carbon felt on the performance of a proton exchange membrane fuel cell. (June 2015) - Hung, Chih-Jung; Liu, Ching-Han; Wang, Chien-Hsun; Chen, Wei-Hung; Shen, Chin-Wei; Liang, Heng-Chia; Ko, Tse-Hao
Abstract: This study concerns the use of conductive carbon material with different content and structure to produce carbon fiber paper for use in proton exchange membrane fuel cells, and investigates how changes in the content and structure of the conductive carbon material influence fuel cell performance. In this study, phenolic resin is used as a conductive carbon material, and is subjected to heat treatment at temperatures of 700 °C, 1000 °C, and 1400 °C, which changes its structure. Before carbon fiber paper is prepared from carbon felt, the felt is treated with phenolic resin solutions with resin content of 5, 10, 15, 20, 25, and 30 wt%. During fuel cell testing, torsion of 40, 60, 80, 100, and 120 kgf-cm is applied. The study found that when the phenolic resin content is 15 wt%, the heat treatment temperature 1400 °C, the test area 25 cm 2, and the test temperature 65 °C, a fuel cell can achieve a current density of 2020 mA cm −2 at 0.5 V and torque of 120 kgf-cm. Highlights: A new method can effectively increase the GDL conductivity and still have excellent permeability to improve FC performance. Use of phenolic resin as a conductive carbon material in the preparation carbon fiber paper. Research on how the conductivity and fuel gas transmission of the conductive carbon material affects PEMFC performance. Discussion of the effect of the structure of conductive carbon material on FC performance at different torsion levels.